Indication and Outcome of Abdominal Re Exploration in Pediatric Population. A Single Centre Experience - Abdullah, Farooq; Gulnaz, Nadia; Ur Rahman, Fayaz; Daraz, Muhammad; Amin, Muhammad; Khan, Salam (ADVANCES IN BASIC MEDICAL SCIENCES, 2022)
Objective Abdominal re exploration (ARE) is an important complication of abdominal surgery and has an effect on morbidity and mortality. The purpose of this study is to know the grounds for performing re-exploration and its effect on outcome. Methodology This retrospective observational study was carried out in pediatric surgery unit of abc teaching hospital from May 2017 to May 2019. All patients below 16 years age that underwent redo abdominal exploration within 60 days of the initial procedure were included in the study. Patients who had initial surgery at another hospital were excluded from the study. We reviewed the data regarding demography, indication for first surgery, indication for ARE, interval between first surgery and redo surgery. Collected demographic and clinical data were analysed using SPSS 20. Results A total of 55 re-explorations were done in a duration of 2 years. Age range from 0.06 to 168 months (Mean 41±5.2months) and percentage of male patients was 64%..On initial presentation, 56% cases were emergency cases and 44% were elective. Common indications for re-exploration were intestinal obstruction 29.1%, peritonitis 16.4%, complications of stoma 16.4%, burst abdomen 10.9%. Mean interval from initial surgery was . Conclusion Abdominal re-exploration is mainly indicated for intestinal obstruction and peritonitis. Anastomotic disruption and Inter loop adhesions are the common surgical finding during ARE. Mortality rate is high in patients re-explored for peritonitis, fecal fistula, abdominal collection and wound dehiscence. Keywords: Abdominal re-exploration (MeSH), Burst abdomen, (Non-Mesh) Re-laparatomy (Mesh).